Developmental Expression of Ecdysone-Related Genes Associated With Metamorphic Changes During Midgut Remodeling of Silkworm Bombyx mori (Lepidoptera:Bombycidae). Issue 1 (22nd August 2016) - Goncu, Ebru; Uranlı, Ramazan; Selek, Gozde; Parlak, Osman
Abstract: Steroid hormone 20-hydroxyecdysone is known as the systemic regulators of insect cells; however, how to impact the fate and function of mature and stem cells is unclear. For the first time, we report ecdysone regulatory cascades in both mature midgut cell and stem cell fractions related to developmental events by using histological, immunohistochemical, biochemical and gene expression analysis methods. Ecdysone receptor-B1 (EcR-B1) and ultraspiracle 1 (USP-1) mRNAs were detected mainly in mature cells during programmed cell death (PCD). Lowered E75A and probably BR-C Z4 in mature cells appear to provide a signal to the initiation of PCD. E74B, E75B and BR-C Z2 seem to be early response genes which are involved in preparatory phase of cell death. It is likely that βFTZ-F1, E74A and BR-C Z1 are probably associated with execution of death. EcR-A and USP2 mRNAs were found in stem cells during remodeling processes but EcR-B1, USP1 and E74B genes imply an important role during initial phase of metamorphic events in stem cells. BHR3 mRNAs were determined abundantly in stem cells suggesting its primary role in differentiation. All of these results showed the determination the cell fate in Bombyx mori (Linnaeus) midgut depends on type of ecdysone receptor isoforms and ecdysone-related transcription factors.